Advertising of medical devices on the Internet - Vargas Portillo, Patricia (Opción, 2020)
Nowadays, Internet is increasingly being used to acquire pharmaceuticals, food supplements and medical devices. Although there is a set of rules established in this regard, they are not sufficient. For this reason, the industry has established a list of ethical standards that complement them, benefiting all sectors that interact in this area